A EAACI drug allergy interest group survey on how European allergy specialists deal with β‐lactam allergy. Issue 6 (17th February 2019) - Torres, Maria Jose; Celik, Gulfem Elif; Whitaker, Paul; Atanaskovic‐Markovic, Marina; Barbaud, Annick; Bircher, Andreas; Blanca, Miguel; Brockow, Knut; Caubet, Jean‐Christoph; Cernadas, Josefina Rodrigues; Chiriac, Anca; Demoly, Pascal; et al.
Abstract: An accurate diagnosis of β‐lactam (BL) allergy can reduce patient morbidity and mortality. Our aim was to investigate the availability of BL reagents, their use and test procedures in different parts of Europe, as well as any differences in the diagnostic workups for evaluating subjects with BL hypersensitivity. A survey was emailed to all members of the EAACI Drug Allergy Interest Group (DAIG) between February and April 2016, and the questionnaire was meant to study the management of suspected BL hypersensitivity. The questionnaire was emailed to 82 DAIG centres and answered by 57. Amoxicillin alone or combined to clavulanic acid were the most commonly involved BL except in the Danish centre, where penicillin V was the most frequently suspected BL. All centres performed an allergy workup in subjects with histories of hypersensitivity to BL: 53 centres (93%) followed DAIG guidelines, two national guidelines and two local guidelines. However, there were deviations from DAIG recommendations concerning allergy tests, especially drug provocation tests. A significant heterogeneity exists in current practice not only among countries, but also among centres within the same country. This suggests the need to re‐evaluate, update and standardize protocols on the management of patients with suspected BL allergy. Abstract : Allergy testing in immediate and nonimmediate reactors to betalactams. The combination of amoxicillin plus clavulanic acid and amoxicillin alone was the most commonly involved BL, although differences among countries concerning the most common penicillin involved exist. All centres performed an allergy workup in subjects with histories of hypersensitivity to BL although there were heterogeneity and deviations from DAIG recommendations concerning allergy tests. Data from this survey suggest the need to re‐evaluate, update and standardize protocols on the management of patients with suspected BL allergy.